2017
DOI: 10.1002/2017gl074172
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a low bulk crustal density for Mars from gravity and topography

Abstract: Knowledge of the average density of the crust of a planet is important in determining its interior structure. The combination of high‐resolution gravity and topography data has yielded a low density for the Moon's crust, yet for other terrestrial planets the resolution of the gravity field models has hampered reasonable estimates. By using well‐chosen constraints derived from topography during gravity field model determination using satellite tracking data, we show that we can robustly and independently determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
119
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 34 publications
20
119
0
2
Order By: Relevance
“…Neumann et al () have estimated the pore‐free density of this soil‐free rock to be 3,060 kg/m 3 . With a porosity of 10%, the bulk density becomes 2,754 kg/m 3 , which is close to the average bulk density given in Goossens et al (). Conversely, as the depth sensitivity of admittance analysis is difficult to evaluate, it is possible that the estimate of Goossens et al () is only sensitive to a portion of the upper crust that has been reworked by sedimentary processes and which has a high intrinsic porosity (see Lewis et al, , for an estimate of the density of near‐surface sedimentary deposits in Gale crater).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Neumann et al () have estimated the pore‐free density of this soil‐free rock to be 3,060 kg/m 3 . With a porosity of 10%, the bulk density becomes 2,754 kg/m 3 , which is close to the average bulk density given in Goossens et al (). Conversely, as the depth sensitivity of admittance analysis is difficult to evaluate, it is possible that the estimate of Goossens et al () is only sensitive to a portion of the upper crust that has been reworked by sedimentary processes and which has a high intrinsic porosity (see Lewis et al, , for an estimate of the density of near‐surface sedimentary deposits in Gale crater).…”
Section: Discussionsupporting
confidence: 86%
“…Note that in both cases, the degree of divergence is generally close to the maximum investigated degree of this study and should not affect the result (Table ). We think that these are due to the regularization procedure applied to small wavelengths for the model of Goossens et al (). No significant differences were found using the JGMRO_120 model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effective density was also employed in (Besserer et al, ) and Han et al () to infer vertical variations in addition to the lateral variations. In Goossens et al (), we showed that applying this constraint to a pre‐GRAIL data system results in a bulk density estimate for the Moon close to that obtained from GRAIL data, 2550 kg m −3 (Wieczorek et al, ). The effective density spectrum for the RM1‐constrained solution presented in that work stays stable for its entire degree range.…”
Section: Introductionsupporting
confidence: 63%
“…However, gamma-ray measurements can only map the uppermost 10 cm of the crust, and little is known about the HPE distribution in deeper layers. In addition, the difference in crustal thickness between the northern and southern hemispheres (the so-called crustal thickness dichotomy) can be reduced if the crustal density varied between the two hemispheres (Goossens et al, 2017;Plesa et al, 2016). The results are non-unique; inferred crustal thicknesses vary between 30 and 87 km for uniform crustal densities between 2,700 and 3,200 kg/m 3 Wieczorek & Zuber, 2004).…”
Section: Introductionmentioning
confidence: 99%